From Theocentric to Anthropocentric: Reconfiguring Tawḥīd in Contemporary Islamic Thought - Saitul Mahtir; Fathorrahman; Aldi Hidayat; Ibnu Azka; Fathur Baldan Haramain (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
This article examines the paradigm shift in tawḥīd from a theocentric–eschatological orientation to an anthropocentric framework by integrating the ideas of Ismāʿīl Rājī al-Fārūqī and Ḥasan Ḥanafī. Employing a qualitative, analytical–epistemological approach, Thomas S. Kuhn’s framework is used to trace the stages of normal science, anomaly, crisis, and paradigm revolution within the discourse of tawḥīd. Conceptual data are drawn from the principal works of both thinkers and analyzed comparatively and integratively. The findings reveal that the theocentric–eschatological paradigm continues to dominate Islamic scholarship and remains insufficiently responsive to contemporary humanitarian challenges. Al-Fārūqī’s tawḥīd-based principles, encompassing the unity of God, creation, truth–knowledge, life, humanity, and the reciprocity of reason and revelation, provide a multi-sectoral Islamic worldview. Meanwhile, Ḥanafī’s reinterpretation of classical kalām themes, particularly the doctrine of divine attributes, offers operational dimensions for transforming consciousness and guiding social praxis. Their integration produces an anthropocentric tawḥīd that supports the renewal of Islamic sciences, ethical–humanitarian agendas, and educational policy. This study contributes to restoring Islam’s vital élan as both a transformation of consciousness and a spectrum of exemplarity, offering a framework for contextual scholarly responses to the paradigmatic crisis facing Muslims in the digital age.